2022
DOI: 10.1186/s40795-022-00574-z
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition among hospitalized children 12–59 months of age in Abyan and Lahj Governorates / Yemen

Abstract: Background The analysis of acute malnutrition in 2018 for the Integrated Phase Classification of Food Security in Yemen shows that high malnutrition rates are present in Abyan governorate (23%) and Lahj governorate (21%). This analysis was community based addressed all children and mostly due to problems related to food intake. The role of diseases was not yet addressed in Yemen. The aim of this study is to assess acute and chronic malnutrition among hospitalized children at 12–59 months of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…16 Al-Waleedi et al reported that 21% of sick children in Yemen had global acute malnutrition (GAM). 17 In Thailand, it was reported that 14.3% of hospitalised children had acute undernutrition, while 23.6% had chronic undernutrition on the basis of anthropometric measurements. 18 A study of 116 hospitalised children aged 1-15 years in Indonesia found the prevalence of malnutrition to be 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…16 Al-Waleedi et al reported that 21% of sick children in Yemen had global acute malnutrition (GAM). 17 In Thailand, it was reported that 14.3% of hospitalised children had acute undernutrition, while 23.6% had chronic undernutrition on the basis of anthropometric measurements. 18 A study of 116 hospitalised children aged 1-15 years in Indonesia found the prevalence of malnutrition to be 28.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of malnutrition classification which weight for age in the present study according to the data collected from the entire country was 45.4% (n = 279), and no statistically significant difference was noted between anthropometric measurements obtained upon admission to and on discharge from the intensive care unit. In a study of 951 pediatric patients involving females at a rate of 51.6%, the rate of acute malnutrition was 21.3% and the rate of chronic malnutrition was 41.3% (23). In a study evaluating the data of a total of 293 pediatric patients in the neonatal and pediatric intensive care unit in the Netherlands, the rate of malnutrition was found to be 24%, and when the patients were evaluated according to the duration of malnutrition, 15% had acute, 20% had chronic and 24% had acute/chronic malnutrition.…”
Section: Discussionmentioning
confidence: 99%